2003
DOI: 10.1021/cg034051u
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of a Desired Metastable Polymorph by Pseudoseeding, Crystal Structure Solution from Its Powder X-ray Diffraction Data, and Confirmation of Polymorphic Transition

Abstract: Described are the successful, selective crystallization and characterization of one (δ-form) of the metastable polymorphs of (±)-[2-[4-(3-ethoxy-2-hydroxypropoxy)phenylcarbamoyl]ethyl]dimethylsulfonium p-toluenesulfonate (1a), which is assumed to exist as a transient key-intermediate crystalline phase relevant to the mechanism of Preferential Enrichment, an unusual enantiomeric resolution phenomenon observed upon crystallization of a certain kind of racemates from solvents. By pseudoseeding the supersaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Thus far, we have found four types of solvent-assisted solid-to-solid transformations of a kinetically formed metastable γ-form crystalline phase into a thermodynamically more stable one (α-, α 1 -, δ-, or ε-form) [5,6,[20][21][22][23][24][25][33][34][35][36][37][38][39][40][41][42][43][44][45], which are relevant to the occurrence of preferential enrichment, in a process of crystal growth.…”
Section: Mechanism Of Preferential Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, we have found four types of solvent-assisted solid-to-solid transformations of a kinetically formed metastable γ-form crystalline phase into a thermodynamically more stable one (α-, α 1 -, δ-, or ε-form) [5,6,[20][21][22][23][24][25][33][34][35][36][37][38][39][40][41][42][43][44][45], which are relevant to the occurrence of preferential enrichment, in a process of crystal growth.…”
Section: Mechanism Of Preferential Enrichmentmentioning
confidence: 99%
“…Among them, the δ-form and α 1 -form crystals are most commonly found for the compounds showing preferential enrichment [20][21][22][23][24][25][33][34][35][36][37][38][39][40][41][42][43][44][45], while only one case is observed for each of the α-and ε-forms [5,6,21,22,39]. In this section, the crystal structures of the δ-and α 1 -forms are described in detail, because this crystal structure provides a crucial information on the mechanism of the polymorphic transition causing preferential enrichment.…”
Section: Stable Formsmentioning
confidence: 99%
“…[3,9,19,20] Compound (AE )-1 c was found to be a new type (k form) consisting of a heterochiral 2D sheet structure, which is quite different from the d form essential for preferential enrichment to occur ( Figure 7 and Table 2). [5,7] This kform crystal structure is characterized by a heterochiral 1D chain along the c axis, which is formed by 1) two kinds of intermolecular hydrogen bonds between the hydroxy group and the nearest amide NH (O···N distance: 3.156 ) and between the same hydroxy group and an oxygen atom of the nearest sulfonate group (O···O distance: 2.524 ) and 2) the O···Br contact (O···Br distance: 3.475 ) arising from the Coulombic donor-acceptor interaction between the methoxy oxygen atom and the nearest bromine atom.…”
Section: Solubilitymentioning
confidence: 99%
“…[3][4][5][6][7][8] Mechanistically, it has been revealed that preferential enrichment is a secondary, dynamic enantiomeric-resolution phenomenon caused by the solvent-assisted solid-to-solid transformation of a metastable g-polymorphic form into a thermodynamically stable d form (or e form in a specific case) during crystallization from the supersaturated solution of a certain kind of racemic mixed crystals (i.e., solid solutions or pseudoracemates) composed of the two enantiomers (Figure 1). [3,7,8,9] Accordingly, a certain mode of polymorphic transition has turned out to be crucial to the occurrence of preferential enrichment. Therefore, on the basis of the elucidated mechanism of this unique polymorphic transition observed for a series of racemic samples that can show preferential enrichment, it may become possible to induce preferential enrichment for their structurally analogous racemic samples, which cannot exhibit this phenomenon, by controlling the mode of the polymorphic transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation